2000
DOI: 10.1002/1529-0131(200010)13:5<270::aid-anr5>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Physical function among older adults with knee pain: The role of pain coping skills

Abstract: Objective.To evaluate the association between pain coping skills and disability among older adults with knee pain.Methods. Baseline measures from 394 older adults with knee pain and disability who participated in a 30-month observational study were analyzed. Pain coping skills were correlated with selfreported disability and walking distance after controlling for covariates of disability. Results.Pain coping skills were significantly associated with disability (P Ͻ 0.05) and distance walked (P Ͻ 0.05). Less ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…However, American Indians who chose to endure painful symptoms were significantly older (mean age ϭ 62.0 years) than persons who used pain control (mean age ϭ 55 years) or who ignored their pain (mean age ϭ 43 years, F[2,33] ϭ 3.50, P ϭ 0.042). Negative thoughts and catastrophizing, which have been associated with poor psychological outcomes (25)(26)(27) and greater physical disability (28), were generally absent in the narrative responses during indepth interviews with the current sample. These findings underscore the cultural value of embracing and adapting to present circumstances but highlight the subtlety that might be expected in communications related to pain.…”
Section: Discussionmentioning
confidence: 73%
“…However, American Indians who chose to endure painful symptoms were significantly older (mean age ϭ 62.0 years) than persons who used pain control (mean age ϭ 55 years) or who ignored their pain (mean age ϭ 43 years, F[2,33] ϭ 3.50, P ϭ 0.042). Negative thoughts and catastrophizing, which have been associated with poor psychological outcomes (25)(26)(27) and greater physical disability (28), were generally absent in the narrative responses during indepth interviews with the current sample. These findings underscore the cultural value of embracing and adapting to present circumstances but highlight the subtlety that might be expected in communications related to pain.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies of both elderly and young people have found an association between the use of the catastrophizing strategy and functional disability (Jensen, Turner & Romano, 2007;Turner, Jensen & Romano, 2000;Turner, Jensen, Warms & Cardenas, 2002;Rapp et al, 2000). Similar results have been found for the prayer strategy (Dozois, Dobson, Wong, Huges & Long, 1996;Lin & Ward, 1996;Rapp et al, 2000). For other coping strategies such as ignoring the pain and distracting oneself, results have been inconclusive.…”
mentioning
confidence: 52%
“…Also, it has been shown that some psychological factors are better predictors of one's adaptation to pain than the magnitude of the pathophysiological damage itself (Murphy, Dickens, Creed & Berstein, 1999;Rapp et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that patients with chronic knee OA who have a positive pain coping attitude exhibit higher functional levels and less pain complaints. 48,49,78 …”
Section: Body Mass Nutritional Supplements and Viscosupplementationmentioning
confidence: 99%